Carbon footprint assessment of a typical low rise office building in Malaysia using building information modelling (BIM) - Shafiq, N. (Taylor and Francis Ltd., 2015)
Concrete and steel are considered the main structural building materials in today's construction. A fair amount of carbon footprint known as embodied carbon footprint is released during their extraction to ultimate utilisation in construction activities. However, quantification and evaluation of the embodied carbon footprint from structural materials of various grades was lacking. This study aimed to evaluate the variation in embodied carbon footprint potential when various classes/grades of concrete and steel in six different combinations were adopted during the design and planning phase using life-cycle analysis (LCA). Building information modelling (BIM) was utilised to virtually construct a two-storey conventional office building, and embodied carbon footprints for each of the six models were quantified. The study highlighted that up to 31 of embodied carbon footprint was avoided from the building. Model M1 (G25XS280) yielded the highest whereas model M4 (G35XS460) was the lowest in contribution. The study also concluded that a considerable amount of reduction in carbon footprint is possible simply by adopting different classes of structural construction materials. The results are expected to help the designers to select best combination of structural materials in future. Â© 2015 Taylor & Francis.